Knowledge and frequency of contacts as factors in forming primary school children attitudes towards peers with developmental disabilities - Slađana Đorem; Gordana Odović; Ana Lukić; Jelena Milić; Milena Božinović; Bojan Joksimović (Биомедицинска истраживања, 2021)
Introduction: Higher level of knowledge and frequent contacts with peers with disabilities can influence the emergence of more positive attitudes of students towards peers with disabilities. In regard to that, our aim was to test the importance of knowledge, contact frequency and other possible factors influencing attitudes of students toward disabled peers. Methods: The study included 140 students of 4th and 5th grade of primary schools. The research was conducted in the period from December 2020 to March 2021 in two primary schools. The Chedoke McMaster scale was used to examine students' attitudes toward peers with disabilities, while Contact with Disabled Persons Scale and the Children's Knowledge about Handicapped Persons Scale were used to assess frequency of contact and knowledge about disabilities. Results: Girls showed a significantly higher level (25.21±6.21) of frequency of contacts with students with disabilities compared to boys (19.66±7.30) (p=0.043) and higher level of knowledge (27.88±5.88) about disabilities compared to boys (25.50±4.69) (p=0.009). Respondents who attended school together with children with disabilities (31.07 ± 8.41) showed a significantly higher level of frequency of contacts with students with disabilities compared to respondents who did not attend school with peers with disabilities (13.72±6.32) (p=0.001). Conclusion: Higher level of knowledge and frequent contacts with peers with disabilities does not have influence on the emergence of more positive attitudes of students towards peers with disabilities.
Keywords: attitudes; primary school students; disability